Pemuatan Foto dan Papan Nama Notaris di Instagram sebagai Bentuk Pelanggaran Kode Etik Notaris di Kota Malang - Rachmawati, Suci; Fadli, Moh. (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This paper aims to analyze the publishing of photographs and notary signs on Instagram as a violation of the notary code of ethics and the efforts of the Malang City Honorary Council to provide sanctions regarding violations of the notary code of ethics. This type of research is empirical juridical research. Data collection uses observation, interviews, and documentation. The results of the study show that loading photos and signage on Instagram is a form of violation of the notary code of ethics. The efforts of the Malang City Honorary Council to overcome violations of the Notary Ethics Code is to impose sanctions following the violations that have been committed.